The semiotics of the character in Ziouani's novel "Kamarad" and its role in introducing African culture. Semiotic study - gana, khalifa (El Omda in Linguistics and Discourse Analysis, 2025)
If the nucleus of the family and society is the individual, then the nucleus of the narrative discourse is the character, to which all the technical components of the narrative are linked: narrative, time, place, events and dialog, in addition to its close relationship with real life and society. The issue of this study is the extent to which the approach of "the semiotics of the character" in the novel "Kamarad" by Al-Zewani is able to reveal the culture of the African man, because the character is a semiotic sign that includes the duality of the signifier and the signified. This study aimed to uncover the renewal of the Algerian novel in terms of theme, content, and presentation, and to highlight the features of African culture based on the novel "Kamarad", which dealt with the phenomenon of irregular migration, and to identify the implicit cultural patterns hidden behind the semiotic meanings